Keanekaragaman Jenis Tumbuhan Paku (Pteridophyta) di Kawasan Wisata Air Terjun Jurang Nganten Kabupaten Jepara - Windari, W; Perwati, Lilih Khotim; Murningsih, M (Bioma : Berkala Ilmiah Biologi, 2021)
Ferns (Pteridophyta) have a high diversity of species and are able to live in a variety of environmental conditions. Ferns have an ecological function (ground cover, producer, bioindicator) and economically (as food, medicine, and crafts). The Jurang Nganten Waterfall in Jepara Regency is a tourist attraction as well as a source of irrigation for rice fields and gardens. The study aims to find out how the diversity of the fern species in the Jurang Nganten Waterfall Tourism Area. The research was conducted at three stations: Station 1 (entrance post), Station 2 (mahogany garden), and Station 3 (around the waterfall). Each station was divided into 7 plots with sizes 5 m x 5 m (terrestrial) and 10 m x 10 m (epiphyte). The results obtained 24 species included in 19Â  genera and 11 families (21 terrestrial species and 3 epiphytic species). The species of ferns that can be found at all stations are Nephrolepis biserrata, Antrophyum plantagineum, Pityrogramma calomelanos, and Pteris biaurita. The highest fern species diversity index (Hâ€™) is at around the waterfall, which is 2.51.Â